Health care in the United States: How the determinants of health insurance status differ across regions - Welle, Derek John (School of Economics, 2019)
Using a nationally representative sample of individuals across all fifty United States from the 2016 American Community Survey (ACS), this research explores differences in the incidence and predictors of health insurance status across region (i.e. West, Midwest, South, and Northeast) for individuals age 18 and older. The data suggests that: 1) Individuals from the Northeast are the most likely to have some form of health insurance, while individuals from the South are the least likely; 2) The factors which influence health insurance status are relatively similar across all regions, though they often differ substantially in magnitude; 3) In some cases region can play a significant role in determining the type of insurance an individual has (i.e. Public versus Private). Policy makers will find these results useful to target specific factors within regions that may prove to increase the number of insured individuals. Furthermore, researchers may choose to use this paper as a current reference and starting point for further in-depth analysis on targeted factors within specific regions.